Chitosan/PCL nanoparticles can improve anti-neoplastic activity of 5-fluorouracil in head and neck cancer through autophagy activation. (May 2021) - de Lima, Jefferson Muniz; Castellano, Lucio Roberto Cançado; Bonan, Paulo Rogério Ferreti; de Medeiros, Eliton Souto; Hier, Michael; Bijian, Krikor; Alaoui-Jamali, Moulay A.; da Cruz Perez, Danyel Elias; da Silva, Sabrina Daniela
Graphical abstract: Highlights: Synthetized composite sponges of chitosan solution (CS)-decorated polycaprolactone (PCL) were able to improve 5-fluorouracil efficacy in head and neck cancer cell lines. The presence of PCL was not related to the drug release rate but it decreased the material porosity. There is a high potential for clinical translation of CS-decorated PCL nanoparticles as drug delivery carrier to improve therapeutic efficacy and reduce local recurrence. Abstract: Head and neck squamous cell carcinoma (HNSCC), a prevalent cancer worldwide, has a high incidence of loco-regional dissemination, frequent recurrence, and lower 5-year survival rates. Current gold standard treatments for advanced HNSCC rely primarily on radiotherapy and chemotherapy but with limited efficacy and significant side effects. In this study, we characterized a novel 5-fluorouracil (5-FU) carrier composed of chitosan solution (CS) and polycaprolactone (PCL) microparticles (MPs) in HNSCC preclinical models. The designed MPs were evaluated for their size, morphology, drug entrapment efficiency (EE%) and in vitro drug release profile. The anti-cancer activity of 5-FU-loaded particles was assessed in HNSCC human cell lines (CAL27 and HSC3) and in a preclinical mouse model (AT84) utilizing cell proliferation and survival, cell motility, and autophagy endpoints. The results demonstrated a 38.57 % in 5-FU entrapment efficiency associated with reduced 5-FU in vitro release up to 96 h post-exposure. Furthermore, CS-decorated PCL MPs were able to promote a significant inhibition of cancer cell proliferation based on the metabolic and colony formation assays, in comparison to controls. In contrast, CS-decorated PCL MPs did not influence the pharmacological efficacy of 5-FU to inhibit in vitro cancer cell migration. Last, cell protein analysis revealed a significant increase of autophagy and cell death evaluated by LC3-II expression and PARP1 cleavage, respectively. In summary, these results support the potential utility of CS-decorated PCL MPs as an effective 5-FU-delivery carrier to improve HNSCC therapeutic management.